The Influence Quality Of Goods And Service Quality On Consumer Statisfaction Of Ano Abadi Meubel Cikatomas - Isep Yoansyah; Arga Sutrisna; Depy Muhamad Pauzy (Journal of Indonesian Management, 2022)
The purpose of this study was to determine the effect of the quality of goods and service quality simultaneously or partially on consumer statisfaction of Ano Abadi Meubel Cikatomas. Survey of Ano Abadi Meubel consumers in Cikatomas. The research method used is descriptive and verification method. The sample in this study amounted to 100 respondents. Data collection was carried out using a questionnaire. The data analysis used is multiple regression analysis. The results of this study indicate that quality of goods and service quality simultaneously have a significant effect on consumer statisfaction. Partially, quality of goods has no significant effect on consumer statisfaction. Partially, the service quality has a significant effect on consumer statisfaction.